A molecular investigation on lignin thermochemical conversion and carbonaceous organics deposition induced catalyst deactivation. (15th November 2021) - Chen, Cheng; Volpe, Roberto; Jiang, Xi
Highlights: Ni nanocrystal surrounded by coke surrogate molecules are constructed to study coke deposition. The surface atoms of Ni nanocatalyst at unsaturated sites show high mobility and premelting tendency. Deposition mechanism is found to be the interactions of molecular collision, thermal dynamics and kinetics. Covalent bonds formed between adsorbates and surface atoms help to preserve catalyst crystallinity. Abstract: Surface coking is the primary deactivation pattern of metal-based catalyst in biofuel reforming, which hinders the commercial utilisation of biomass. In this study, molecular dynamics simulation with reactive force field is performed to investigate the surface instability induced thermal degradation of Ni nanocatalyst and coke deposition induced catalyst deactivation. Coke deposited on catalyst surfaces is a complex mixture of carbonaceous organics. Coke surrogate models containing polycyclic aromatic hydrocarbons (PAHs) and oxygenated aromatics are proposed to reflect the molecular size and O/C ratio based on the molecular structures identified during lignin pyrolysis and soot inception mechanism. Lindemann index is used to characterize the degree of crystallinity of catalyst. It is found that atoms at unsaturated sites of outer shell show high mobility and tend to modify the coordination number distribution. Mechanisms behind the effects of temperature, PAH size and oxygen content on coke adsorption are revealed from three aspects of molecular collision dynamics, thermal dynamics and kinetics. The modification of crystallinity of catalyst outer shell and the occurrence of seeping after coke adsorption would affect the subsequent catalyst regeneration. This study is expected to provide guidance on the design of anti-coking catalyst, evaluation of catalyst regeneration and reactor optimisation.